Challenging glaucoma with emerging therapies: an overview of advancements against the silent thief of sight - Sarkis, Solange; Chamard, Chloé; Johansen, Bianca; Daien, Vincent; Michon, Frederic (Frontiers in Medicine, 2025)
Glaucoma, a leading cause of irreversible blindness, represents a significant challenge in ophthalmology. This review examines recent advancements in glaucoma treatment, focusing on innovative medications and creative strategies. While new agents offer promising methods for lowering intraocular pressure (IOP), they also pose challenges related to efficacy and side effects. Alongside IOP reduction, emerging neuroprotective approaches are being explored to safeguard retinal ganglion cells (RGCs) from glaucoma-induced damage. The review also evaluates the potential of novel drug delivery systems, such as biodegradable implants and nanoparticles, to enhance treatment effectiveness and patient adherence. Additionally, it highlights the role of personalized medicine in identifying new biomarkers and customizing therapies based on individual genetic and environmental factors.